Heat transfer during drop impingement onto a hot wall: The influence of wall superheat, impact velocity, and drop diameter. (June 2020) - Gholijani, A.; Schlawitschek, C.; Gambaryan-Roisman, T.; Stephan, P.
Highlights: The influence of the wall superheat, impact velocity and drop diameter on hydrodynamics and heat transport are investigated. The experimental results agree with numerically predicted spreading radius and heat flow. The heat flow during advancing and receding phases rises with increasing of wall superheat, impact velocity and drop diameter. The maximum spreading radius decreases with increasing wall superheat. Abstract: The present work addresses the influence of the wall superheat, drop impact velocity, and impact diameter on hydrodynamics, heat transport, and evaporation during drop impingement onto a heated solid wall in a pure vapor atmosphere. A generic experimental setup has been designed and built with a temperature-controlled cell that allows investigation of drop impingement in a pure vapor atmosphere. Therein a single drop is generated and falls onto a heated surface due to gravity. The experiments are conducted with refrigerant FC − 72 . The heated surface is formed by a thin metallic layer coated onto an infrared transparent glass, so that the temperature field of the solid-fluid interface can be observed from below with an infrared camera at high spatial and temporal resolution. The heat flux field is derived from the temperature field using a dedicated post-processing procedure. The dynamic evolution of contact line radius is derived using image analysis. The drop shape is observed with a high speed camera, which is synchronized with the infrared camera. Experimental and numerical results for contact line radius and heat flow evolution are compared with each other. This gives an insight to the governing heat transport mechanism during different phases of drop impingement. Experimental and numerical parameter studies reveal that higher wall superheats, higher impact velocities, or larger drop diameters each result in increasing heat flow after the impact. The maximum spreading radius after impingement is increasing with rising impact velocity or impact diameter, and decreasing with rising wall superheat.